2019
DOI: 10.1186/s12913-019-4718-5
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cancer screening service utilization and associated factors among HIV positive women attending adult ART clinic in public health facilities, Hawassa town, Ethiopia: a cross-sectional study

Abstract: BackgroundIn Ethiopia, cervical cancer is a public health concern, as it is the second most cause of cancer deaths among reproductive age women and it affects the country’s most vulnerable groups like; rural, poor, and HIV-positive women. Despite the strong evidence that cervical cancer screening results in decreased mortality from this disease, its utilization remains low.MethodsAn institution-based cross-sectional study was conducted from March 2 to April 1/2019 to assess the level and factors affecting util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
52
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 31 publications
14
52
2
Order By: Relevance
“…Only the variable having 0 to 8 years of schooling was independently associated with a higher likelihood of having HPV infection, and this finding is in agreement with other Brazilian study 9 . Low education has been an important barrier to preventive measures for HPV infection, just as low education has been associated with difficulties in accessing screening tests for cervical cancer 21,22 …”
Section: Discussionsupporting
confidence: 89%
“…Only the variable having 0 to 8 years of schooling was independently associated with a higher likelihood of having HPV infection, and this finding is in agreement with other Brazilian study 9 . Low education has been an important barrier to preventive measures for HPV infection, just as low education has been associated with difficulties in accessing screening tests for cervical cancer 21,22 …”
Section: Discussionsupporting
confidence: 89%
“…Primarily, among 24 studies, two case-control studies [24,41] were not considered in the prevalence estimation. Additionally, three studies [20,22,26] were excluded from prevalence estimation after checking funnel plot and the significance of Egger's regression test. But, they were not excluded from meta-analysis for risk factors.…”
Section: Meta-analysis Publication Biasmentioning
confidence: 99%
“…Despite this case, the findings of a study conducted in different settings indicated that there was low uptake of cervical cancer screening services [9][10][11][12][13][14]. Lack of awareness, poor attitude towards cervical cancer screening, and poor perception of the severity of the disease were some of the factors for not up taking the screening service.…”
Section: Introductionmentioning
confidence: 99%